Public expenditure, growth, and poverty reduction in rural Uganda - Fan, Shenggen; Zhang, Xiaobo (Wiley, 2008)
Using district-level data for 1992, 1995, and 1999, the study estimated effects of different types of government expenditure on agricultural growth and rural poverty in Uganda. The results reveal that government spending on agricultural research and extension improved agricultural production substantially. This type of expenditure had the largest measured returns to growth in agricultural production. Agricultural research and extension spending also had the largest assessedimpact on poverty reduction. Government spending on rural roads also had a substantial marginal impact on rural poverty reduction. The impact of low-grade roads such as feeder roads is larger than that of high-grade roads such as murram and tarmac roads. Education's effects rank after agricultural research and extension, and roads. Government spending in health did not show a large impact on growth in agricultural productivity or a reduction in rural poverty. Additional investments in the northern region (a poor region) contribute the most to reducing poverty. However, it is the western region (a relatively well developed region) where most types of investment have highest returns in terms of increased agricultural productivity.